Determinants of Dropout from and Variation in Adherence to an Exercise Intervention: The STRRIDE Randomized Trials. Issue 1 (2022) - Collins, Katherine A.; Huffman, Kim M.; Wolever, Ruth Q.; Smith, Patrick J.; Siegler, Ilene C.; Ross, Leanna M.; Hauser, Elizabeth R.; Jiang, Rong; Jakicic, John M.; Costa, Paul T.; Kraus, William E.
ABSTRACT: Purpose: This study aimed to characterize the timing and self-reported determinants of exercise dropout among sedentary adults with overweight or obesity. We also sought to explore variations in adherence among individuals who completed a 6- to 8-month structured exercise intervention. Methods: A total of 947 adults with dyslipidemia (STRRIDE I, STRRIDE AT/RT) or prediabetes (STRRIDE-PD) were enrolled to either control or to 1 of 10 exercise interventions, ranging from doses of 8 to 23 kcal·kg −1 ·wk −1, intensities of 50% to 75% V˙O2 peak, and durations of 6 to 8 months. Two groups included resistance training, and one included dietary intervention (7% weight loss goal). Dropout was defined as an individual who withdrew from the study because of a variety of determinants. Timing of intervention dropout was defined as the last session attended and categorized into phases. Exercise training adherence was calculated by dividing weekly minutes or total sets of exercise completed by weekly minutes or total sets of exercise prescribed. General linear models were used to characterize the associations between timing of dropout and determinant category. Results: Compared with exercise intervention completers ( n = 652), participants who dropped out ( n = 295) were on average non-White (98% vs 80%, P < 0.01), had higher body mass index (31.0 vs 30.2 kg·m −2, P < 0.01), and were less fit at baseline (25.0 vs 26.7 mL·kg −1 ·min −1, P < 0.01). Of those who dropped out, 67% did so before the start of or while ramping up to the prescribed exercise volume and intensity. The most commonly reported reason for dropout was lack of time (40%). Notably, among individuals who completed the ramp training period, subsequent exercise intervention adherence did not waiver over the ensuing 6–8 months of training. Conclusions: These findings are some of the first to delineate associations between the timing of dropout and dropout determinants, providing guidance for future exercise interventions to better support individuals at risk for dropout.